Rainwater harvesting as an alternative water resource in Malaysia: potential, policies and development. (10th July 2016) - Lee, Khai Ern; Mokhtar, Mazlin; Mohd Hanafiah, Marlia; Abdul Halim, Azhar; Badusah, Jamaludin
Abstract: Some regions in Malaysia is facing water scarcity problem nowadays despite Malaysia has high quantity of water resources. The increasing water demand has triggered the initiatives to look for alternative water supply. Rainwater harvesting was proposed by the government as part of the solutions to mitigate water scarcity problem. Literatures associated with rainwater harvesting were obtained from various sources. These literatures were reviewed and have been instrumental to analyze the potential, policies and development of rainwater harvesting in Malaysia. This article discusses the potential of rainwater harvesting in Malaysia under the dynamic climate as a case study. The challenges of rainwater harvesting development in terms of environment, policy, economy, social and technical are pointed with the way forward for rainwater harvesting. It is anticipated that rainwater harvesting is going to play the role as an alternative water resource in the country. In order to promote rainwater harvesting in Malaysia, inter-ministerial and multi-stakeholders co-operations are needed to mainstream this alternative water resource into the national strategy. Highlights: RWH was proposed by the government to mitigate water crisis. Malaysian government has implemented guidelines with regard to RWH. RWH needs to be streamlined into national policy. Inter-ministry co-operation is needed to promote RWH.